Ensuring the safety of employees of metallurgical enterprises in the conditions of sustainable development - Tverdokhliebova, N. E.; Yevtushenko, N. S. (My University, 2023)
Ensuring the safety of workers of metallurgical enterprises is an important element of sustainable development in this industry.
Keywords: safety; metallurgical enterprises; sustainable development